A Numerical Study on Fire Development in a Confined Space Leading to Backdraft Phenomenon - Aleksander Król; Małgorzata Król; Stanisław Krawiec (Energies, 2020)
This paper presents the results of numerical experiments on fire development and the backdraft phenomenon. The numerical model of fire development built with the use of Ansys Fluent was then validated based on literature data taken from real fire experiments. Some theoretical foundations of airflow and combustion modelling were added. Some features of the numerical model, which allowed for its high accuracy to be achieved, were widely discussed. Since large buoyancy forces were involved, to reproduce the decrease of the atmospheric pressure with height, a variable static pressure was applied using UDF (user-defined function).The results showed good accordance taking into account both the temperature profiles and the distribution of the airflow velocity. Once the model was validated, the research was extended to examine the backdraft phenomenon. The results revealed characteristic phases of the phenomenon and the occurrence of the gravity current as well, which were reported by empirical experiments.